PENGARUH KADAR GABUS DALAM BAGASE DAN PERSENTASE SODA TERHADAP SIFAT UNDI HITAM DAN PULP (The influence of pith content in bagaae and percentage of sodium hydro:dde on the properties of black liquor and pulp) - Bambang Wiyono; Surdiding Ruhendi; Kumia Sofyan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
In this investigation, the pith content of the bagaBBe samples were 10, .20, and 30 psrcent. Cookinf trials incoporated varioulpercentt11es of soda (NaOH) bei'ltf 15, 18, and .20 percent, concecutively. The cbndition applied were tiB follow temperature, 11(f C (maintained for one hour), and the ratio of bagaBBe liquor bei111 1 : ''3. 76. The results were anolyd using the factorial design with a si111le replicate.Experimental results show that the increase in pith content gave a signifieant effect on. the raidual allcaliand(reeneBB. The increasi111 of NaOH percentage provided liighly significant effect on the ash content, Kappa number, and brightness. The. increasingof NaOH also provided a significan teffect on the residualalkali. The increasingof pith contenttend to grow up residual alkali (Y 0.84650 + 0,18433 X) and freeness (Y= 13.08718 + 0.13333 X). Produced by 16'% NaOH, the residual alkali posse1111ed a lower significant effect than 18 and 20% NaOH, as well as, NaOH of 18% owned a lower than .20%. Furthermore, NaOH of 16% produced Kappa number a higher higly significant effect than 18 and aO% NaOH, and 18% NaOH owned a higher than 20%. The percentages increase of pith in bagaseto 80% produced Bimiliar to.from bagasse of 10% pith content.